Adverse reactions of different COVID-19 vaccines among healthcare professionals: A qualitative study in Mosul, Iraq - Shahad M. Khaleel; Sadeel A. Shanshal; Mohammed I. Aladul (Elsevier, 2022)
Background: COVID-19 disease was highly infectious causing a declaration of a global pandemic and the scientists believed that developing a safe and effective vaccine was the solution. Various vaccine candidates were announced by different health authorities. Many factors affect the acceptance of vaccines. This study aims to explore the perceptions, attitudes, and expectations of healthcare professionals (HCPs) toward COVID-19 vaccines. Method: A qualitative study approach was conducted by using face-to-face semi-structured interviews with HCPs in Mosul city, Iraq. Results: Twenty-five HCPs participated in the interviews. After qualitative analysis four main themes emerged: perception of vaccines; participants believed that vaccines were vital inventions, motivations to take the vaccine; most HCPs were motivated based on the scientific evidence regarding COVID-19 vaccines, expectations about the safety and efficacy of COVID-19 vaccines; participants had different opinions based on the type of the vaccine and the available data, side effects experienced; severe side effects were expected but only mild adverse reactions were experienced by the majority. Conclusion: HCPs had good knowledge about COVID-19 vaccines which was not affected by rumors and misinformation. In contrast to their expectations, the experienced side effects of the first and the second doses were mild to moderate in severity. The majority of HCPs based their choice of the vaccine on the efficacy and safety profile of the available options.